(untitled) (Hekima Review, 2006)
So many books have been published on the Second Vatican to the point that one can wonder what new another book on the topic can bring. This book belongs in fact to an eight book series, Rediscovering Vatican II, published in commemoration of the 40th anniversary of this great Church event of the last century. Each book of the series tries through historical analysis of the birth of council documents, to make an evaluation of how the documents have been accepted, implemented or rejected, and what direction the church trough these documents is heading to.